MENINGKATKAN PRESTASI BELAJAR SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI EKOSISTEM PADA SISWA KELAS X FARMASI I SMK MUHAMMADIYAH 5 BABA - Sumarni (Transpublika Publisher, 2023)
This research is motivated by class problems regarding the lack of student motivation in learning biology learning outcomes experienced by students. Corrective action learning is carried out to solve problems by applying a problem-based learning model. The problem-based learning model is a model of learning activities in which the process of implementing learning goes through the following steps, first by observing, asking, exploring, associating and communicating. Both in this learning model describe everything that exists in our environment, especially those related to subject matter objects, so that learning becomes meaningful, and can develop student learning outcomes. By implementing the learning model in biology subjects as a learning method, it can be seen that there is a correlation of learning motivation and has shown a satisfactory increase in learning outcomes.